Pengembangan Sistem Mutu untuk Informasi Akuntansi Rumah Sakit - Defia Nurbatin; Pudji Lestari (Jur. Akuntansi, Politeknik Negeri Malang, 2019)
The purpose of research to produce hospital accounting information system based on quality system form Standard Operational Procedure (SOP) and Flow Chart as guide of income information on service of patient BPJS to separate with general patient at RSU.Universitas Muhamadiyah Malang. The type of research is research development with approach model of Design Based Research (Purwiyanto, 2014). Methods of data collection are observation, interview and Questionnaire. Technique of data analysis used is Technique percentage result of validation score from user response and expert validation team related to product design feasibility. This study produces 10 SOPs and 5 cash flow cash flow charts that demonstrate the application of SOP and effective flow chart to be implemented, proved the result of the average percentage of feasibility is very effective and according to user needs.Keywords: Hospital Accounting, Quality System